Development of Pop Up Book Media to Improve Motivation and Learning Outcomes of Natural and Social Sciences for Grade IV Elementary School - Marsanda Salwa Nisrina; Fitria Dwi Prasetyaningtyas (Postgraduate, University of Mataram, 2025)
The lack of enthusiasm of students in participating in learning due to the limitations of teachers to make creative and interesting learning media in IPAS subjects on Indonesian cultural assets material makes learning interest and learning outcomes low. This study aims to create pop up media that illustrates Indonesian cultural assets to increase the interest and learning outcomes of fourth grade students of SD Negeri 2 Protomulyo, Kendal Regency and analyze the effectiveness and feasibility of the pop up book media developed. This research uses the 10 stages of the Borg and Gall model for R&D research. Data were collected through observation, interview, documentation, questionnaire and test techniques. The results of the media data analysis were declared very feasible by material experts and media experts with a percentage of 93%. The effectiveness of the media was tested using the N-Gain test obtained a value of 0.56 in the medium category, this value indicates that the pop up book succeeded in improving student learning outcomes, feasible and effective in improving student learning outcomes. This is evidenced by an increase in interest in learning which makes student learning outcomes increase after learning with pop up book media